Taking Psychoanalytic and Psychometric Perspectives toward a Binocular Vision of Religion - Keller, Barbara (Brill research perspectives in religion and psychology, 2020)
Current psychology of religion relies mostly on quantitative psychometric approaches for the description, explanation, or prediction of religious experience and behavior, risking narrow reifications of operational definitions and neglect of individual experience. Psychoanalytic concepts are rarely addressed, due to being seen as lacking a scientific foundation, such as hypothesis testing based on large samples. Psychoanalysts have been slow to discuss religion without suspicion of pathology. Recently, psychoanalysts have broadened their empirical work and a “narrative turn” is discernible in developmental and personality psychology, allowing the inclusion of subjective perspectives. Drawing on these developments a rapprochement of psychodynamic and psychometric approaches is suggested to gain more depth of vision. Examples are given for the areas of development, personality, and psychotherapy.